Efeito da suplementação de magnésio na capacidade de sprint repetido em crianças de 9 14 anos - Lundberg, Kezianne Roseno de Castro (2019)
Magnesium appears as an element of interest for scientific community because it’s involved in rapid energy production reactions through phosphagenic pathway. Besides, it’s considered important for collective sports performance since this modality depends on adequate energy supply during the movement, particularly for collective modalities characterized by short duration and high intensity movements. Thus, magnesium supplementation should be a strategy to increase sportive indexes and making different components of physical fitness improvements possible for collective sports. The aim of the present study was to verify the effect of 350mg / day supplementation with oxide magnesium on young volleyball players repeated-sprint ability during sports initiation. Eighteen children, aged 9 to 14 years, both sexes, who were randomized in two groups: the experimental, who received the supplementation, and the control, who ingesed placebo for 30 days took part in the study. All participants were submitted to blood sample collections for required components biochemical dosages and performed repeated sprints-ability test at pre and post intervention moments. Repeated measures ANOVA (time x condition) was used to verify interaction effects between groups. Results showed there was no interaction effect between the groups for subjects with normal serum magnesium concentrations, although non significant time effect for the sprint variables was observed for experimental group.